(untitled) (Archive of Conferences, 2020)
Agriculture in the Bukhara Emirate was well developed and the wealth of the population was one of the highest in Central Asia. This wealth is comparable to the wealthy Khanate of Kokand. Agriculture lands of the Emirate were situated along the Valley, which included Rivers of Zerafshan, Shahrisabz and Oxus. Other lands were irrigated artificially via channels and manmade irrigation systems such as aryk. In the areas far from the river and creeks, continuous heat and dry air affected the growth of the plants and trees very negatively. From March to May, only the lands between the cities of Bukhara and Karshi as well as the areas between the river Oxus and Miankol valley flourished. In the Emirate, most commonly grown grains were wheat, millet, barley, bulrush and corn. Wheat was usually sown either in winter or in spring. The first produce was usually harvested at the end of May and the second was collected at the end of September or October. One batman1of wheat cost from 16 Tenge 2 to 1 Tilla 3(from 3 Roubles 20 kopeek to 4 Roubles). Rice cultivation was only enough for internal consumption. Barley was sown twice, in early spring and autumn and was collected in May or in autumn. Its price was 8 Tenge for a batman. Millet sown in small amounts, however, it gave rich yields and its price was 5-6 Tenge per batman. Corn was sown at the end of April and yielded in July to feed animals. Another harvest was collected during August or September for the people to consume. Corn was one of the cheapest grains and was a popular food consumed among commoners of the Emirate. The cost of corn was 7 Tenge per batman. Another common agriculture product was cotton. Cotton was sown in spring and collected during the early autumn. From the cottonseeds, cooking oil was produced. Cotton fields required regular irrigation. The cotton was the main export item to Russia priced at 4 Tilla (16 Roubles) per batman. Another common agriculture product was alfalfa (lucerne), which was collected 4-5 times in the summer and its price was 1 Tenge (20 kopeek).